Pemanfaatan Aplikasi Asana Sebagai Platform Digital Kolaboratif dalam Meningkatkan Produktivitas Proyek Mahasiswa - Anggraini, Zifa; Santoso, Hudi (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to describe the initial implementation of the Asana application as a digital collaborative media in student projects, the impact on student project productivity, and the evaluation of the implementation. The background of this study is the need to resolve various problems in the project team, such as lack of task transparency, miscommunication, and late completion. This study uses a qualitative descriptive approach, data is collected through observation, documentation of activities in the Asana application, field notes during the implementation process and supported by literature studies. This study was conducted using the Technology Acceptance Model (TAM) theory and also digital transformation. The results show that the use of Asana has a positive impact on increasing student productivity, especially in terms of time management, more structured division of work, and more efficient communication time. In addition, the evaluation revealed advantages such as clear work visualization and increased individual responsibility, as well as disadvantages such as the need for adaptation and dependence on internet connections. Recommendations are directed at initial training, development of digital learning modules, and ongoing evaluation. These findings strengthen the relevance of collaborative technology in supporting digital transformation in higher education environments.